Reconstruction of series of annual runoff Nura river (Journal of Geography and Environmental Management, 2016)
The article specifies the previously available data on the rate of the annual water river basin. Nura using observation data to 2006 inclusive. New data on the rate of flow of very short series of observations (up to 6 years). Used with new guidance on the definition of normal flow.
Keywords: annual runoff; river-analogue